Performance of structural lightweight oil palm shell concrete incorporating high volume ground granulated blast furnace slag / Mo Kim Hung - Mo, Kim Hung (2015)
With the growing amount of environmental issues associated with the use of conventional concrete-making materials, there is a need to utilize alternative materials to reduce the dependency on such materials and preserve the environment. Commonly, granite and river sand, which are both non-renewable materials, are used as coarse and fine aggregate in concrete respectively. Furthermore, the process of obtaining these materials is usually not environmental friendly, such as blasting of rocks and excavation of river beds. Another major environmental issue caused by concrete manufacturing is through the use of cement, which is commonly associated with high amount of carbon dioxide emission during its production. This investigation is therefore aimed towards producing sustainable structural grade lightweight oil palm shell concrete (OPSC) incorporating high volume ground granulated blast furnace slag (GGBS) and analysing the behaviour of such concrete. The use of waste materials such as oil palm shell (OPS) and manufactured sand was targeted to reduce the dependency of conventional granite and river sand as coarse and fine aggregate in concrete, respectively. Whereas GGBS, which is a processed industrial by-product, was utilized as partial cement replacement in this study. In the first part of the study, the effect of GGBS at varying cement replacement level between 20 – 70% on the mechanical and some durability-related properties of OPSC was investigated. Although the inclusion of up to 60% GGBS resulted in strength reduction of the OPSC, the cost- and environmental-efficiencies of the concrete were improved; investigation on some durability-related properties of OPSC also revealed improved performance through the use of 20% GGBS as cement replacement level. In addition, the GGBS-blended OPSC was found to be feasible in terms of the structural performance such as bond properties and flexural behaviour of beams and adhered to the stipulations in codes of practices. In order to enhance the applicability of the OPSC, the second part of the study dealt with the analysis and prediction of the structural behaviour of the reinforced concrete beam subjected to flexural loading. The moment-rotation approach was introduced in this regard to explore the possibility of utilizing such approach as a design tool for the OPSC in the future. The required partial interaction properties, such as bond stress-slip and compressive stress-strain relationship of OPSC were derived and formulated to be used in the moment-rotation approach. Results showed that the predicted moment-deflection behaviour of the OPS RC beam using the moment-rotation approach were close to that obtained from the experiment and also compared favourably to published results for RC beams incorporating other types of LWC. In addition, the use of closed-form solution which is based on the moment-rotation approach was found to give good estimate of the serviceability behaviours such as mid-span deflection, crack spacing and crack width. In short, the results obtained demonstrated the feasibility of including GGBS to produce a sustainable lightweight OPSC without significantly compromising the material and structural properties while the structural behaviour of the GGBS-blended OPSC in RC beams could be well-predicted using the moment-rotation approach.